2017
DOI: 10.1515/botcro-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Archaeobotanical components of grave goods in prehistoric tumuli 6 and 7 at the archaeological site of Kaptol-Gradci, near Požega (Croatia)

Abstract: The Iron Age site of Kaptol-Gradci belongs to the south-eastern periphery of the Hallstatt cultural complex, dominated primarily by the Kaptol cultural group, and encompasses a hillfort settlement and necropolis. During the investigation campaigns organized to date, 25 tumuli have been identified and 17 of them investigated. This paper presents the first results of the analysis of plant remains from a Hallstatt necropolis in Croatia, from tumuli 6 and 7, identified as an integral part of the complex burial rit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Orah (Juglans) i kesten (Castanea) vjerojatno su se proširili u rimsko doba (Schmidt i sur. 2000;Šoštarić 2005). Razvoj vegetacije posljednjih 2000 godina u sredozemnom dijelu Hrvatske nije najbolje istražen, no detaljnije je bio analiziran na vlažnom području Blatuša (botanički rezervat Đon, srednja Hrvatska), gdje su prije dva tisućljeća prevladavale bukovo-hrastove šume.…”
Section: Palinološka Istraživanja U Hrvatskoj: Primjer čEpićkog Poljaunclassified
“…Orah (Juglans) i kesten (Castanea) vjerojatno su se proširili u rimsko doba (Schmidt i sur. 2000;Šoštarić 2005). Razvoj vegetacije posljednjih 2000 godina u sredozemnom dijelu Hrvatske nije najbolje istražen, no detaljnije je bio analiziran na vlažnom području Blatuša (botanički rezervat Đon, srednja Hrvatska), gdje su prije dva tisućljeća prevladavale bukovo-hrastove šume.…”
Section: Palinološka Istraživanja U Hrvatskoj: Primjer čEpićkog Poljaunclassified
“…Systematic studies of plant remains found in burials have a long tradition (Jacomet, Kreuz 1999), but in Poland such studies are still scarce so far; they have only become more popular in recent years (among others Pińska et al 2015;Pińska, Drążkowska 2020;Badura et al 2022). Meanwhile, the results of botanical analyses significantly enrich the ethnographic information on funeral customs in various regions and periods of human history (Lempiäinen-Avci et al 2017;Šoštarić et al 2017;Riera Mora et al 2018) and on plant symbolism in funeral contexts (Dafni et al 2006;Galera et al 2013;Badura et al 2022). They often provide information concerning the timing of burial and the status of the deceased (Nadel et al 2013, p. 11776;Kelso, Miller 2016, p. 166;Ives 2021).…”
Section: Introductionmentioning
confidence: 99%